Differences in performance on English and Hebrew versions of the MoCA in Parkinson's patients. (2020) - Xu, Yaqian; Mirelman, Anat; Saunders-Pullman, Rachel; Mejia-Santana, Helen; Caccappolo, Elise; Raymond, Deborah; Giladi, Nir; Bressman, Susan; Marder, Karen; Alcalay, Roy N.
Abstract: Introduction: The Montreal Cognitive Assessment (MoCA), an instrument widely used for cognitive screening in Parkinson's disease (PD), is validated in Hebrew and English. However, it remains unknown whether the scores are comparable. Methods: The MoCA was analyzed in 483 Ashkenazi Jewish PD patients in Tel-Aviv and New York who had MoCA ≥21. Each section of the MoCA was compared between English and Hebrew. Linear regression models were used to test the association between MoCA performance and language. Results: Total MoCA scores were lower in Hebrew than in English (25.4 versus 26.1; P = 0.007), even after adjustment for age, sex, PD duration, genotype, levodopa equivalent dose, the Unified Parkinson's Disease Rating Scale (UPDRS-III), and Geriatric Depression Scale score in a linear model ( P < 0.001). However, when language sections were removed from the total, scores were similar between the languages (Hebrew 23.7 versus English 23.4, P = 0.111). Conclusion: The language section of the MoCA may be more difficult in Hebrew. The comparability of MoCA in different languages requires further evaluation. Highlights: Total MoCA scores were lower in Hebrew-speaking than in English-speaking Parkinson's patients. The language section in the Hebrew version of the MoCA may be more difficult. Merging data from cognitive testing performed in different languages requires caution.